Bodotria paraspinifera sp. nov. (Crustacea: Cumacea: Bodotriidae), a new Korean cumacean - Kim, Sung-Hyun; Lee, Chang-Mok; Kim, Young-Hyo (Zootaxa, 2020)
This study on Korean cumaceans is based on the specimens collected from Geomun Island in Korea. The one species of the Genus Bodotria (Bodotriidae) is identified as new species, Bodotria paraspinifera sp. nov., which is similar to B. spinifera Gamô, 1986 in having the spinulose on body, dorso-lateral carina of carapace well-developed, carapace almost rectangular in dorsal view, carpus of pereopod 1 dilated, pereopod 2 without ischium, and uropod endopod uniarticulate. However, shape of carapace anterior portion, spinulose distribution pattern, and setae patterns and segment ratios of appendages are characteristics which serve to distinguish the new species from B. spinifera. Herein we described with full illustration containing information of the mouthparts for the new species. Also, a key to the Korean Bodotria species is provided.